(untitled) (Mongolian Journal of Astronomy and Geophysics, 2024)
The increasing seismic activity around the Mongolian capital Ulaanbaatar city since 2005 year has been identified as occurring along two active faults that extend west and northwest of Ulaanbaatar city and are perpendicular to each other. The Emeelt fault (40 km long, approximately 15 km northwest of Ulaanbaatar city) is located. The length and geomorphology of these faults indicate that an earthquake of magnitude 6.5-7.5 occurred. After the earthquake, the weakened soil around the fault was weathered during a long time period, and the shape, size, and location of the faults on the fault plane have become unknown, and the geomorphology was changed greatly. However, the GPR survey method, one of the advanced technologies in modern geophysics, is an excellent method for identifying faults by mapping radar wave reflections and has been proven to be effective and widely will use in the future. We conducted detailed integrated geological and geophysical surveys on Emeelt active faults in the Ulaanbaatar city region in 2010-2012 to determine their parameters, and in order to confirm some of these results, we present in this article some of the results of additional geophysical surveys conducted on the Emeelt active fault in 2023. In this research, we conducted a survey to determine some geometric parameterssuchasfaultlocationanddipangleusingmeasurementsof250MHzand100MHzGPRantennas.